Ordinary and extraordinary prices in the Giolito Libri spirituali sales List - Giliola Barbero (JLIS.it, 2018)
This article illustrates an early modern sales list of books, the Libri spirituali di stampa of the Venetian Giolito publishing house. This printed list, kept in the Biblioteca Comunale Augusta in Perugia, includes the descriptions of 81 devotional and religious sixteenth century books with their prices expressed in Venetian lire (an account money). The aim of the research is to illustrate the price policy of the Giolito firm between 1587 and 1592, and the segment of the market they intended to serve. For this purpose, on the basis of the books priced, the list has been dated and placed in chronological relation with other already known Giolito sales catalogues. In the second part of the article, average prices per printing sheet are calculated and the relationships between prices and dates, languages and formats are taken into consideration. In the end, the reasons why some few editions were proposed on the market at a higher price are discussed. The list is published in the Appendix.